Effects of persistent energy-related brine contamination on amphibian abundance in national wildlife refuge wetlands. (December 2018) - Hossack, Blake R.; Smalling, Kelly L.; Anderson, Chauncey W.; Preston, Todd M.; Cozzarelli, Isabelle M.; Ken Honeycutt, R.
Abstract: To inform sustainable energy development, it is important to understand the ecological effects of historical and current production practices and the persistence of those effects. The Williston Basin is one of North America's largest oil production areas and overlaps the Prairie Pothole Region, an area densely populated with wetlands that provide important wildlife habitat. Although historical disposal practices that released chloride-rich waters (brines) produced during oil extraction into the environment are no longer used, brine spills still occur frequently. We sampled 33 wetlands for three amphibian species in Montana and North Dakota during 2015–2017, primarily on National Wildlife Refuges, and used N-mixture models to determine how abundance varied with evidence of brine contamination. To provide insight into effects of historical versus contemporary contamination, we also estimated the association of well density and age with water quality and amphibian abundance. Abundance of boreal chorus frog ( Pseudacris maculata ) larvae declined most rapidly in response to increased chloride (range: 0.04–17, 500 mg/L), followed by the northern leopard frog ( Lithobates [ Rana ] pipiens ) and barred tiger salamander ( Ambystoma mavortium ). Water quality and population- and community-level abundance of amphibians were more strongly related to nearby wells (≤800 m) installed before 1982 than to wells installed since 1982. These results suggest historical brine management practices were the primary driver of contamination and reduced amphibian abundance in wetlands we sampled, reflecting multi-decadal ecological effects. These persistent effects also underscore the critical need for tools to restore landscapes affected by brine contamination.